Game-Based Learning: Alternative Approaches to Teaching and Learning Strategies in Health Sciences Education - Zijing Hu (Educational Process: International Journal)
Background/purpose. Game-based learning has received increased attention in health sciences education in the global north due to its effectiveness in achieving learning outcomes. The literature concurs that learning outcomes can be improved through appropriate pedagogical approaches. However, more studies need to focus on game-based learning in the health sciences and higher education field in South Africa. This study aimed to explore acupuncture students’ lived experiences with game-based learning at an identified South African university.